2022
DOI: 10.1108/nfs-09-2021-0267
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention of prebiotics and vitamins on gut health of children

Abstract: Purpose Gut health has multidimensional impact on childhood growth and development. Diet being the major modulator of gut health, this study aims to hypothesize if supplementation of dietary prebiotics and vitamins can impact gut environment of healthy children. Design/methodology/approach A double-blind placebo-controlled trial was conducted with parallel allocation of children 8–13 years of age to placebo or test group. Test group was supplemented with 1.5 g of formulation comprising prebiotics and vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Studies have shown that a persistent imbalance of the gut microbiota is related to diabetes, obesity, and CVD [ 49 ]. Among several factors, diet and dietary constituents play a vital role in maintaining and improving the beneficial microbiota [ 50 , 51 ].…”
Section: Microbiota and Cardiometabolic Diseasesmentioning
confidence: 99%
“…Studies have shown that a persistent imbalance of the gut microbiota is related to diabetes, obesity, and CVD [ 49 ]. Among several factors, diet and dietary constituents play a vital role in maintaining and improving the beneficial microbiota [ 50 , 51 ].…”
Section: Microbiota and Cardiometabolic Diseasesmentioning
confidence: 99%